Dari CLE ke SLE: Laporan Kasus dari Rumah Sakit Setempat: Laporan Kasus - Kelvin; Louis Rianto; Linda Julianti Wijayadi (PT Kalbe Farma Tbk., 2025)
Introduction: Lupus erythematosus (LE) is a combination of various interrelating autoimmune clinical diseases. Cutaneous lupus erythematosus (CLE) is a spectrum of typical autoimmune skin features of systemic lupus erythematosus (SLE). A good recognition of the typical appearance of this skin lesion (CLE) enables diagnosis and good management of SLE. Case: A 26-year-old female with SLE with acute skin lessions (ACLE) skin lesions. Suspicion of SLE became stronger when the antinuclear antibody (ANA) titer reached 1:3,200. The main therapy is methylprednisolone injection followed by a gradual dose reduction. The patient was treated for 6 days in hospital and all lesions improved. Conclusion: The patient in this case had SLE with 6 clinical domains in the EULAR/ACR 2019 criteria and a total score of 34 (>10). Earlier and more accurate diagnosis of SLE can make therapy more effective, especially if CLE is already present.